Survey Paper on Fraud Detection in Medicare Using Machine Learning - S. , Muthulakshmi; S. , Priyadharshini; P.S. , Sanjana; R. , Anupriya (International Journal of Psychosocial Rehabilitation, 2020)
Healthcare plays a major role in the growing population. Medicare systems provide effective remedies for the affordable healthcare systems. Increasing processing power, availability of big data, and advancements in statistical modeling have been accelerated due to the adoption of machine learning. There are recent fraudulent activities detected in Medicare systems. It takes a lot of time for humans to read, collect, categorize, and analyze the data. These fraudulent activities in Medicare systems, which can be tremendously reduced by using machine-learning methods. The survey currently focuses on the algorithm that contributes better results to fraud detection. Our survey predicts the comparative analysis in the detection of fraudulent activities using the various algorithm techniques.